2018
DOI: 10.1093/jcr/ucy039
|View full text |Cite
|
Sign up to set email alerts
|

Why Am I Seeing This Ad? The Effect of Ad Transparency on Ad Effectiveness

Abstract: Given the increasingly specific ways marketers can target ads, many consumers and regulators are demanding ad transparency: disclosure of how consumers' personal information was used to generate ads. We investigate how and why ad transparency impacts ad effectiveness. Drawing on literature about offline norms of information-sharing, we posit that ad transparency backfires when it exposes marketing practices that violate norms about "information flows"-consumers' beliefs about how their information ought to mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
4
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(140 citation statements)
references
References 59 publications
4
121
4
11
Order By: Relevance
“…Even if users are aware of these mechanisms, they usually do not proactively look for them, or expect the explanations to be 'pretty obvious'. In line with [6], we observed that users were dissatisfied with explanations that are not specific enough. Particularly in the case of very specific recommendations, users expect that they are targeted to a very specific group and do not believe an overly vague or generic explanation (like 'reaching out to a broad audience').…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Even if users are aware of these mechanisms, they usually do not proactively look for them, or expect the explanations to be 'pretty obvious'. In line with [6], we observed that users were dissatisfied with explanations that are not specific enough. Particularly in the case of very specific recommendations, users expect that they are targeted to a very specific group and do not believe an overly vague or generic explanation (like 'reaching out to a broad audience').…”
Section: Discussionsupporting
confidence: 79%
“…For this purpose, Facebook's ad system provides three types of explanations: ad-specific explanations ("Why am I seeing this ad"), general explanations ("About Facebook Ads") and ad settings. In a recent study, Kim et al [6] came to the rather obvious conclusion that more transparency would increase ad effectiveness if the associated data collection practices would be deemed acceptable; unacceptable data collection practices (such as tracking outside of the website or aggressive profiling and inference of user traits) would decrease ad effectiveness.…”
Section: Explanations and Transparency Of Advertisementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the self-interested nature of firms, consumers may view commercial persuasion as inherently threatening to their autonomy, even as they engage in voluntary exchanges with firms (Sunstein 2016). Armed with more and more data, firms can micro-target consumers based on their own past choices and unique characteristics, posing new challenges to consumer autonomy from privacy violations and lack of explainability (Kim et al 2019). At the same time, consumers are better informed and more aware of their susceptibility to covert influences (Susser et al 2018).…”
Section: Perceived Autonomy In a Changing Marketplace: A Research Agendamentioning
confidence: 99%
“…For example, while transparency is often found to be a positive factor for improving consumer reactions to ads, this is not always the case. Sometimes, transparency in the form of privacy notices is not necessarily desirable because notices can interrupt how information flows (Kim, Barasz, and John 2019). Consumers increasingly desire convenience and smooth transactions online.…”
Section: Issues Arising From Online Behavioral Advertising and Other mentioning
confidence: 99%